Improved reproducibility of carbon-based cesium/formamidinium perovskite solar cells via double antisolvent drippings in adduct approach - Ruankham P. (2023)
High-quality perovskite materials are usually prepared in a non-reactive environment, which increases fabrication costs and poses difficulties in mass production. In this work, the deposition of cesium/formamidinium (CsFA) perovskite under low-cost dry-air conditions was modified to improve both material quality and photovoltaic performance. By using double chlorobenzene drippings in the adduct approach, pinhole-free and smooth CsFA films were achieved. The carbon-based perovskite solar cells (PSCs) using the obtained CsFA films provided an enhanced power conversion efficiency (PCE) with good reproducibility. The main reasons for this achievement are the suppression of charge recombination caused by traps in the perovskite films and the improvement of interface properties. In addition, our proposed method was found to be applicable for reproducible 1 cm × 1 cm solar modules. Our findings open up the possibility for low-cost, simple, and large-scale manufacturing of perovskite-based optoelectronic devices.